Navigating the Path to Islam: Evaluating Persuasive Communication in Conversion Guidance Programs at the Indonesian Chinese Islamic Unity Institute (PITI) in Surabaya - Wulandari, Siti Nur Alfiana; Ihsani, A. Fikri Amiruddin; Bachtiar, M. Anis; Retpitasari, Ellyda (Tribakti: Jurnal Pemikiran Keislaman, 2024)
Understanding Islam poses a significant challenge for newly converted individuals and groups, underscoring the necessity of companionship and guidance to facilitate their learning and exploration of faith. Recognizing this imperative, the Indonesian Chinese Islamic Unity Institute (PITI) in Surabaya has initiated mentoring activities tailored specifically for new converts of Islam. Employing a persuasive communication approach between mentors and converts, the program aimed to deepen their understanding of faith. This study evaluated the effectiveness of persuasive communication in the development of conversion to Islam at the Indonesian Chinese Islamic Association Institute in Surabaya. Using qualitative research methods with a descriptive approach, in-depth interviews with key informants were conducted to gather data. The analytical framework is rooted in the AIDDA concept, encompassing Attention, Interest, Desire, Decision, and Action. The findings reveal that the Surabaya PITI Institute adeptly implements the AIDDA concept in the context of persuasive communication. Beginning with capturing converts' attention through the introduction of the ta'aruf program by da'i, the program proceeds to generate interest by delivering engaging and relevant content. The da'i employs a gentle and persuasive language when imparting Quranic teachings and avoiding coercion. As a result, converts make informed decisions to embrace Islamic practices such as regular prayer, zakat, and fasting, signifying a meaningful behavioral shift towards adherence to Islamic principles. Consequently, converts integrate the teachings presented by the da'i, prioritizing Islamic doctrines derived from the Quran and Hadith while gradually distancing themselves from conflicting Chinese cultural practices. This research provides insights into the role of persuasive communication in guiding converts and offers implications for the development of effective Da'wah strategies and approaches.